CONHECIMENTO, PERCEPÇÃO E ATITUDES DE ADOLESCENTES ESCOLARES REFERENTE AO HPV - Oliveira, Denise de (2021)
Introduction: The human papillomavirus (HPV) is the most common sexually transmitted disease (STD) in the world. The severity of infection lies in its relationship with the development of the cancer of cervix, vulva, vagina, penis, anus, and oropharynx. Objective: The aim of this study was to investigate the adolescent's knowledge regarding HPV, to understand the practices for preventing sexual diseases and early pregnancy, including, verifying which information sources are used to knowledge building regarding awareness and knowledge of sexually transmitted infections. Methodology: The research design was a quali-quantitative approach, carried out through individual recorded interviews, using a semi-structured questionnaire. The sample included adolescents 36 from 12 to 18 years from two schools in the city of Guarapuava/PR, a private and a public school. Results: We observed that the HPV knowledge was generic,superficial and limited, with only a third of the adolescents recognizing the HPV as an STD. Conclusion: The early knowledge about STIs is crucial to avoid contamination. Many of the risk factors may be prevented essentially through awareness and learning of Sexually Transmitted Infections education in schools and family enviroment. The Adolescents' access to information is relevant and essential for building a critical consciousness about safe sex and preventing sexually transmitted diseases.